2011
DOI: 10.3109/10253890.2011.619604
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress and carbohydrate metabolism: Persistent changes and slow return to normalcy in male albino rats

Abstract: The present study tested the hypothesis that long-term repeated exposure to stressors results in irreversible changes in carbohydrate metabolism. Groups of adult male rats (five per group) were restrained for 1 h and 4 h later were forced to swim for 15 min everyday for 2, 4, or 24 weeks; five rats were autopsied after each interval. Groups of five rats exposed to stress for 2 or 4 weeks were maintained without further treatment (recovery groups) for up to 24 weeks. The fasting blood glucose concentration, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
(63 reference statements)
2
18
1
Order By: Relevance
“…It regulates the metabolism by altering the biochemical pathways to achieve stability. Indeed the state of allostasis has been demonstrated by us in rats that were exposed to chronic stress [24]. In this study consistent hyperglycemia was observed in rats for 24 weeks, following exposure to restraint for 1 h followed by forced swimming for 15 minutes after a gap of 4 hours every day for 2, 4 or 24 weeks.…”
Section: Glucose Metabolism Allostasis and Allostatic Loadsupporting
confidence: 84%
See 3 more Smart Citations
“…It regulates the metabolism by altering the biochemical pathways to achieve stability. Indeed the state of allostasis has been demonstrated by us in rats that were exposed to chronic stress [24]. In this study consistent hyperglycemia was observed in rats for 24 weeks, following exposure to restraint for 1 h followed by forced swimming for 15 minutes after a gap of 4 hours every day for 2, 4 or 24 weeks.…”
Section: Glucose Metabolism Allostasis and Allostatic Loadsupporting
confidence: 84%
“…altered physiological processes that may cause damage to the system [43]. For instance in our study [24] prolonged hyperglycemic condition due to stress was accompanied by insulin resistance and failure to tolerate glucose as shown by OGTT in rats. Thus when stress is persistent and it is prolonged for a long duration, the adaptive processes in the body become maladaptive resulting in pathophysiology.…”
Section: Glucose Metabolism Allostasis and Allostatic Loadsupporting
confidence: 47%
See 2 more Smart Citations
“…phosphoenolpyruvate carboxykinase (PEPCK), fructose-1, 6-bisphosphatase and glucose-6-phosphatase (G6Pase) and serves as a mechanism by which the availability of glucose is maintained. An increase in activities of hepatic G6Pase and PEPCK under different stressful conditions has been reported [9][10][11][12]. Hyperglycemia due to increased gluconeogenesis has a negative impact on the body as it results in insulin resistance [13].…”
Section: Introductionmentioning
confidence: 99%